2017
DOI: 10.1111/cen.13410
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between adiposity, bone density and microarchitecture is maintained in young women irrespective of diabetes status

Abstract: Irrespective of the presence of an underlying metabolic condition, young women display a negative relationship between MRI-measured BMA and DXA-based assessment of BMD. Furthermore, an association between BMA and visceral adiposity supports the notion of a common origin of these two fat depots.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
13
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 37 publications
4
13
2
Order By: Relevance
“…Our results also demonstrate reduced BMC or BMD Z-scores and an impairment of the relationship between the fat and muscle tissue. Several previous studies also investigated this association and found similar results [ 16 18 , 20 , 21 , 29 , 44 46 , 58 , 59 ]. Our observations of reduced relative bone strength of T1DM patients, and more so in the poor metabolic control patients, have led us to speculate that maintaining such status may be associated with increased risk of fractures later in life.…”
Section: Discussionsupporting
confidence: 63%
See 4 more Smart Citations
“…Our results also demonstrate reduced BMC or BMD Z-scores and an impairment of the relationship between the fat and muscle tissue. Several previous studies also investigated this association and found similar results [ 16 18 , 20 , 21 , 29 , 44 46 , 58 , 59 ]. Our observations of reduced relative bone strength of T1DM patients, and more so in the poor metabolic control patients, have led us to speculate that maintaining such status may be associated with increased risk of fractures later in life.…”
Section: Discussionsupporting
confidence: 63%
“…It is worth noting that the impairment of the relationship between these components is an important factor in the development of the bone fragility [ 14 , 15 ] and increased risk of fractures [ 22 25 ]. Moreover, other studies showed abnormalities of bone microarchitecture, intra-abdominal fat content, and bone fat marrow [ 18 ]. Also regarding the detection of poor glycaemic control, our study observed negative correlations of total body BMD, BMC, and LBM (Z-scores) with increased HbA1c in type 1 diabetes patients.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations